Epidemiology of sclerotinia stem rot and efficacy of integrated control measures for soybean in Northeast China - Li, Yichu; Liu, Jia; Shi, Fengmei; Ma, Ligong; Zhang, Yunhua; Yu, Liangbin; Meng, Qinglin (Frontiers in Plant Science, 2025)
Background/aimsSclerotinia stem rot (SSR), caused by Sclerotinia sclerotiorum, is one of the most destructive fungal diseases affecting soybeans, and its effective management remains a challenge. This study aimed to investigate the epidemiology of SSR and to evaluate the efficacy of chemical fungicides, biocontrol agents (particularly low-risk, eco-friendly products), cultural practices, as well as to propose integrated strategies for SSR control in soybeans.MethodsBoth small-scale and large-scale field trials were conducted in in Northeast China, the country’s largest soybean-producing region. The soybean varieties included Heinong 48, Kenfeng 16, Hefeng 50, Nongqingdou, Kendou 25, and Kendou 39.ResultsThe epidemiological study characterized the sclerotial germination dynamics and identified key factors influencing the disease severity index (DSI) and soybean yield. Assessment of low-risk, eco-friendly disease control products in small-scale field trials revealed that 6% oligosaccharins achieved the highest control efficacy of 70.0%. These findings informed the development of integrated control measures, which were then evaluated in scale-up field trials. Notably, these control measures significantly reduced disease incidence compared to control fields, demonstrating a disease control efficacy of 64.3–75.3%, alongside a yield increase of 5.7–14.7%. Subsequent implementation of the integrated measures achieved effective disease management, with a control efficacy of 56.41% and consistent yield improvements of 5.76–15.56%.ConclusionsIntegrating disease-resistant variety selection, low-risk/eco-friendly chemical and biological agents, and cultural practices effectively manages SSR in soybean crops, significantly reducing DSI and increasing soybean yield in Northeast China. While these strategies may be applicable in other regions, optimal approaches may vary owing to regional differences and annual variations.